(untitled) (Research, Society and Development, 2020)
Chronic Kidney Disease often implies a strict care regime for the patient due to the Hemodialysis treatment. Having as objective to understand the patient’s care experience in hemodialysis and build a theoretical model that represents this experience. Is about qualitative research, using Grounded Theory as a method. Semi-structured interviews were conducted with 24 subjects: 10 patients undergoing hemodialysis; 7 family caregivers of hemodialysis patients who actively participated in the day-to-day care; and 7 professionals from the multiprofesional team. Data analysis took place with substantive, open and selective coding, and theoretical coding. Was identified that this experience is caused by the category “Starting the care trajectory”, having as intervening conditions the categories “Confronting a new life of care” and “Being cared for”, whose consequence was “Harmonizing- with hemodialysis and its care” in the context of “Transmuting yourself in the face of care for the maintenance of life”. In this way it is concluded that the experience of care is an event that demands learning, modifications and adaptations from the patient. For this, the patient will need emotional, psychological and spiritual support from different sources such as professional, family and social support to be involved satisfactorily in this experience.